2022
DOI: 10.1177/10760296221097383
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1, thrombin-antithrombin, and prothrombin fragment F1+2 have higher diagnostic values than D-dimer for venous thromboembolism after TKA

Abstract: Objective To investigate the diagnostic values of D-dimer, plasminogen activator inhibitor-1 (PAI-1), thrombin–antithrombin (TAT), and prothrombin fragment F1 + 2 (F1 + 2) for predicting venous thromboembolism (VTE) after total knee arthroplasty (TKA). Methods Ultrasonography and CTPA were performed to diagnose VTE in 252 patients who underwent TKAs. Plasma D-dimer, PAI-1, TAT, and F1 + 2 levels were assessed 1–3 days prior to operation (T1), second hour (T2), first (T3), and third day (T4) after the operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Frischmuth et al reported that higher plasma PAI-1 levels were associated with an increased risk of future incident VTE [50]. Yang et al suggested that plasma PAI-1 had a higher predictive value for VTE than D-dimer [51]. Thus, our results together with the above reports, may imply that plasma PAI-1 may be a potential biomarker in the diagnosis of VTE.…”
Section: Discussionsupporting
confidence: 74%
“…Frischmuth et al reported that higher plasma PAI-1 levels were associated with an increased risk of future incident VTE [50]. Yang et al suggested that plasma PAI-1 had a higher predictive value for VTE than D-dimer [51]. Thus, our results together with the above reports, may imply that plasma PAI-1 may be a potential biomarker in the diagnosis of VTE.…”
Section: Discussionsupporting
confidence: 74%
“…TKA patients are at a heightened risk of venous thromboembolism due to the increased risk of endothelial injury caused by tourniquet use, venous stasis due to leg positioning, and the aberrant activation of the clotting cascade. The incidence of VTE can range from 0.7-53%, depending on the preventive measures taken [11,13]. Whether intermuscular vein thrombosis was classi ed as deep vein thrombosis is one of the main reasons for such a large difference.…”
Section: Discussionmentioning
confidence: 99%
“…However, when samples are obtained before stroke, the power of PAI-1 levels to predict future stroke may be limited [9]. Although the correlation between PAI-1 levels and postoperative VTE after THA and TKA has been reported [10,11], the power of PAI-1 levels to predict future VTE is questionable. People homozygous for the 4G allele have the highest and 5G homozygotes have the lowest PAI-1 levels [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has a low positive predictive value and low specificity. More specific markers of venous thromboembolism risk may be listed, i.e., SFMC, TATC, F1 + 2, P- and E-selectin [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%